50. EFFECTIVENESS OF INFORMATION TECHNOLOGY INTERVENTION IN HEALTH STATISTICS REPORTING AT COMMUNE HEALTH STATIONS IN THANH HOA PROVINCE IN 2025 (Vietnam Journal of Community Medicine, 2025)
Background: The current health statistics reporting activities at commune health stations in Vietnam face numerous limitations, affecting data quality and the effectiveness of primary healthcare management. Information technology is a potential solution to improve this situation.Objective: To evaluate the effectiveness of an integrated health statistics reporting software at commune health stations in Thanh Hoa province in 2025.Subjects and methods: A pre-post intervention study was conducted on 238 healthcare staff at 48 commune health stations in Hau Loc and Quang Xuong districts, Thanh Hoa province. The study period was from 15 January 2025 to 30 June 2025. The intervention included the deployment of integrated health statistics reporting software, training, and technical support supervision. The effectiveness of the intervention was assessed through changes in knowledge, practice, and software feature scores.Results: The rate of health workers with adequate knowledge increased from 57.3% before the intervention to 79.4% after the intervention (p < 0.001). The proportion of healthcare staff with adequate practice increased from 91.3% to 94.5% (p = 0.246). The software received high ratings, scoring 4.1 out of 5, particularly in usefulness, information security, management support, reliability, quality of information, support capability, information extraction, and internal connectivity.Conclusion: The integrated health statistics reporting software intervention improved knowledge and practice of health statistics reporting among commune health station staff in Hau Loc and Quang Xuong districts, Thanh Hoa province. The software was highly rated in terms of technical features.
Keywords: Information technology, health statistics, commune health stations, intervention, Thanh Hoa.